2017
DOI: 10.18203/2320-6012.ijrms20171839
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic condylar screws versus 95º angle blade plate fixation of subtrochantric fractures of femur

Abstract: Background: The purpose of this prospective randomized study was to evaluate the results of dynamic condylar screw (DCS) system and 95º angle blade plate fixation in the management of sub-trochanteric femoral fractures, regarding stability, union time, complication rate and functional out come.Methods: Total 30 consecutive patients with sub-trochanteric fracture were studied. The inclusion criteria were closed sub-trochanteric fractures in adults of both gender aged 18 years or above. Pathological fractures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
4
3
0
Order By: Relevance
“…Similarly, Neher et al reported the duration as 108 min of surgery with 95°BP (8) . Also, in agreement with present study, Vashisht et al reported mean duration of surgery for DCS was 82.2 minutes (Range 72-90), mean duration of surgery for 95° BP was 104.47 minutes (Range 95-115) (9) . In present study, regarding blood loss intraoperatively in DCS about 365 cc, while in 95°BP about 440 cc, this due to large incision and more manipulation in BP group.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Similarly, Neher et al reported the duration as 108 min of surgery with 95°BP (8) . Also, in agreement with present study, Vashisht et al reported mean duration of surgery for DCS was 82.2 minutes (Range 72-90), mean duration of surgery for 95° BP was 104.47 minutes (Range 95-115) (9) . In present study, regarding blood loss intraoperatively in DCS about 365 cc, while in 95°BP about 440 cc, this due to large incision and more manipulation in BP group.…”
Section: Resultssupporting
confidence: 93%
“…Current study found that the mean time of union is 15.75 weeks for group treated with DCS & 17.5 weeks for group treated with 95° BP, there were no significant statistical differences of the mean time union between groups (p value 0.07). This was agreed with Vashisht et al who reported that radiological union in most of the patients (14 out of 15 cases) treated with DCS plate occurred between 12-16 weeks, while in cases treated with 95°BP radiological union in most of the patients (13 out of 15) occurred between 14-18 weeks (9) . Rohilla et al showed that union in 16 weeks (11) , Neogi et al in 15.6 weeks (12) , Laghari et al in 16.5 weeks with DCS (13) .…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations